2020
DOI: 10.1111/all.14469
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactive carbohydrate determinant‐specific IgE obscures true atopy and exhibits ⍺‐1,3‐fucose epitope‐specific inverse associations with asthma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
(178 reference statements)
0
16
0
Order By: Relevance
“…The first two related studies, done in urban and rural Ghanaian schoolchildren, showed that anti-glycan IgE responses may be dominant over those of common allergen-specific IgE, namely peanuts [ 44 ], and preferentially associated with Schistosoma infection [ 22 ]. The third study, performed in blood collected from urban and rural Ugandan schoolchildren, showed that aeroallergen-specific IgE tests were more frequently positive than SPT to the same allergens, and also that such serum IgE tests were artificially positive to the tested allergens ( Der pteronyssinus , German cockroaches, and peanuts), since a high proportion of this positivity was attributable to CCD-specific IgE and not to true atopy [ 45 ]. Furthermore, in vitro inhibition of IgE binding to CCDs has been shown to increase diagnostic selectivity of allergen-specific tests [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first two related studies, done in urban and rural Ghanaian schoolchildren, showed that anti-glycan IgE responses may be dominant over those of common allergen-specific IgE, namely peanuts [ 44 ], and preferentially associated with Schistosoma infection [ 22 ]. The third study, performed in blood collected from urban and rural Ugandan schoolchildren, showed that aeroallergen-specific IgE tests were more frequently positive than SPT to the same allergens, and also that such serum IgE tests were artificially positive to the tested allergens ( Der pteronyssinus , German cockroaches, and peanuts), since a high proportion of this positivity was attributable to CCD-specific IgE and not to true atopy [ 45 ]. Furthermore, in vitro inhibition of IgE binding to CCDs has been shown to increase diagnostic selectivity of allergen-specific tests [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Reactivity towards a subset of core N-glycans carrying α-1,3-fucose was inversely associated with asthma. 31 The above mentioned protective factors are part of the environmental exposures pertaining to the so-called hygiene or old friends hypotheses, which further include sibship size, pet ownership, (other) gastrointestinal infections, and environmental biodiversity. 32 Some of the abovementioned epidemiological surveys have explored potential underlying mechanisms suggesting that risk factors might boost inflammatory responses, affect bronchial epithelial barrier function, or associate with the metabolic syndrome, or both.…”
Section: Protective Factorsmentioning
confidence: 99%
“…Although the presence of oligosaccharides on other helminths is well established, there is relatively little evidence regarding the significance of IgE antibodies to these epitopes. A recent study provides evidence that IgE to classical CCD, particularly those with an alpha‐1, 3‐fucose epitope, may not just be an epiphenomenon of parasite exposure but may be implicated in the protective effect of certain environmental and geohelminth exposures against asthma 84 …”
Section: Group D Oligosaccharide Epitopes That Are the Targets For Ige Ab Responses To Schistosomes And Other Helminthsmentioning
confidence: 99%